2014
DOI: 10.17508/cjfst.2014.6.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cookies composition on temperature profiles and qualitative parameters during baking

Abstract: Indexing p. 1  Editorial Bord p. 1  Guide for Authors p. 3  Manuscript preparation p. 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 22 publications
2
20
1
2
Order By: Relevance
“…(2,6) = 1.38 and F (2,6) = 4.67; P = NS all]. Hardness in cookies showed values ranging from 33 to 51 N, which were higher to the 15 N observed in cookies added with up to 4.4% of SCG(Hatem et al, 2018), although the hardness of cookies analyzed in this experiment was much lower than the reported byPereira, Correia, and Guiné (2013) in commercial brands of Maria-type cookies, which ranged from 99 to 159 N, and also lower to the 100 N registered in cookies made entirely with wheat flour and baked at 110°C for 10 min(Budžaki et al, 2014). However, cohesiveness and springiness of the cookies are considered low in comparison with cookies made only with wheat flour such as the Maria-type cookies(Pereira et al, 2013) and similar to the found byHatem et al (2018), in cookies made with a lower amount of SCG on them.…”
contrasting
confidence: 68%
See 1 more Smart Citation
“…(2,6) = 1.38 and F (2,6) = 4.67; P = NS all]. Hardness in cookies showed values ranging from 33 to 51 N, which were higher to the 15 N observed in cookies added with up to 4.4% of SCG(Hatem et al, 2018), although the hardness of cookies analyzed in this experiment was much lower than the reported byPereira, Correia, and Guiné (2013) in commercial brands of Maria-type cookies, which ranged from 99 to 159 N, and also lower to the 100 N registered in cookies made entirely with wheat flour and baked at 110°C for 10 min(Budžaki et al, 2014). However, cohesiveness and springiness of the cookies are considered low in comparison with cookies made only with wheat flour such as the Maria-type cookies(Pereira et al, 2013) and similar to the found byHatem et al (2018), in cookies made with a lower amount of SCG on them.…”
contrasting
confidence: 68%
“…Phenolic compounds provide a potential health benefit to the consumer by its antioxidant activity, and contribute importantly for the taste and flavor of food products (Goleniowski et al, 2013;Shahidi & Nacsk, 2004). The previously stated is important because it has been recognized that taste, flavor, appearance, and texture are very important characteristics which determine food selection by the consumers (Andersen, Brockhoff, & Hyldig, 2019;Budžaki et al, 2014), and for that reason it is recommended to evaluate them during the process of food development. In this sense, the just-about-right (JAR) method applied together with hedonic evaluation allows the food scientist to identify the direction of the changes recommended for the formulation of the food in order to improve the sensory characteristics in products (Ares et al, 2017;Lawless & Heymann, 2010;Li, Hayes, & Ziegler, 2015).…”
mentioning
confidence: 99%
“…Measuring the color of the biscuits in the CIE L*a*b* sys¬tem by using a colorimeter (Konica Minolta Chroma Meter CR-400, Japan) and calculations to determine the change of color were made according to the method described from Budžaki., et al [32].…”
Section: Determination Of Water Activity (A W )mentioning
confidence: 97%
“…These processes influence the qualitative parameters of cookies including colour formation. Browning is the final step of both the Maillard reaction and caramelization, one of the end-points of the baking process and the final result of sugar degradation during baking [17].…”
Section: Resultsmentioning
confidence: 99%
“…The measurement of the colour of the biscuits (at 5 different places on the surface) was evident on the basis of CIE L*, a*, b* color system using a colorimeter (Konica Minolta Chroma Meter CR-400, Japan), and the calculations for the total colour difference (colour change, ΔЕ) are made according to the described from Budžaki et al, [17]. The relation between the calculated value ΔE and the human eye tolerance for perceiving differences between colours is given in Table 1 [18].…”
Section: Methodsmentioning
confidence: 99%